Model Pendidikan Literasi Digital Pada Masyarakat Desa: Strategi Pengembangan Kemampuan Digital Untuk Meningkatkan Kualitas Hidup - Hana Thifal Hanifah; Raisa Az Zahra; Icshan Fauzi Rachman (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
Providing digital literacy education for village communities make public knowledge which teenage social media users feel they must know. The aim of this digital literacy outreach is to know how to manage social media and as an effort to shape the character of teenagers ripe. The focus of the activity subject is the community in the village. Results This activity is the formation of characters such as religion, tolerance, love homeland, friendly/communicative, love peace, likes to read, caring social, and responsibility. The priority problem for village communities is the lack of number and variety of important learning resources for community life that can be easily accessed by village communities and lack of information both directly and via social media.